CRISIS ANALYSIS AND METHODOLOGY THE WAYS OF ITS IMPROVEMENT - LYUDMILA MIKHAYLOVNA Kupriyanova (Мир новой экономики)
The article is devoted to the problems of crisis management, related to the emergence and development of the crisis. Analysis of the works of scientists revealed approaches associated with resource theory and the concept of dynamic abilities in relation to Russian organizations that require additional research. Crisis management strategy has an important role to stabilize the financial and economic state of the Organization in crisis, therefore, must be subject to continuous improvement, take into account the impact of external and internal factors on the development of business should focus on the implementation of measures to prevent and overcome crises and prevent crises in the future. It is recommended that you use the professional competencies of the anti-crisis Director for anti-crisis solutions.